THE TID MODEL FOR MODULATION OF LARGE SCALE ELECTRON DENSITY MODELS - Leitinger R.; Rieger M. (My University, 2005)
Various modern applications of empirical electron density models need realistic structures of the electron density distribution with smaller scales than the model background. Travelling Ionospheric Disturbances (TIDs) produce three dimensional and time dependent disturbances of the background ionization. We present a TID model suitable to «modulate» large scale electron density distributions by multiplication. A model TID takes into account the forward tilt of the disturbance wave front, a distinct vertical structure, a fan type horizontal radiation characteristic, geometric dilution and attenuation. More complicated radiation patterns can be constructed by means of superposition. The model TIDs originate from source regions which can be chosen arbitrarily. We show examples for TID modulations of the background model family developed at Trieste and Graz (NeQuick, COST-prof and NeUoG-plas).
Keywords: ELECTRON DENSITY MODELS; IONOSPHERE; TID MODEL; TRAVELLING IONOSPHERIC DISTURBANCES